2017
DOI: 10.1080/1177083x.2017.1345766
|View full text |Cite
|
Sign up to set email alerts
|

Creating Treaty-based local governance in New Zealand: Māori and Pākehā views

Abstract: This article explores the need for Treaty-based local governance, raised to national prominence by the 2014 outrage against New Plymouth Mayor Andrew Judd, who advocated a Māori ward for 2016. The Treaty of Waitangi influenced the creation of Māori seats in Parliament in the nineteenth century, and a provision for Māori seats in local councils in 2001. There has been limited uptake of the latter and Māori remain significantly underrepresented. Innovations in governing arrangements have allowed non-elected Māor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 12 publications
0
14
0
Order By: Relevance
“…Simmonds, Kukutai, and Ryks () observe that there is a lack of willingness on the part of local authorities to promote forms of Māori representation internally on boards and other decision‐making forums. Webster and Cheyne () found that effective inclusion of Pākehā and Māori in governance arrangements at the local level is a significant requirement as part of the principles of the Treaty of Waitangi. However, Key Informant 7 noted that in the absence of fair and effective representation, attention needs to be given to how local authorities carry out their statutory responsibilities to foster Māori contribution to decision‐making.…”
Section: Results: Indigenous Experiencementioning
confidence: 99%
See 2 more Smart Citations
“…Simmonds, Kukutai, and Ryks () observe that there is a lack of willingness on the part of local authorities to promote forms of Māori representation internally on boards and other decision‐making forums. Webster and Cheyne () found that effective inclusion of Pākehā and Māori in governance arrangements at the local level is a significant requirement as part of the principles of the Treaty of Waitangi. However, Key Informant 7 noted that in the absence of fair and effective representation, attention needs to be given to how local authorities carry out their statutory responsibilities to foster Māori contribution to decision‐making.…”
Section: Results: Indigenous Experiencementioning
confidence: 99%
“…Embracing mana whenua concepts can help build resilient, sustainable regional development pathways that are also inclusive. To exemplify the potential of such pathways, Webster and Cheyne () presented two case studies that illustrate how a meaningful partnership arrangement between local Māori and local governments is a possible outcome in Aotearoa New Zealand and should be sought across rural areas to ensure Indigenous groups are not marginalised in these remote locations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In interviews of Māori and Pākehā leaders from a range of political spheres, Webster and Cheyne reveal a disjunction between Treaty considerations that increasingly inform national policy and governance, and how TAs interact with citizens . They highlight confusion in the interpretation of the Local Government Act 2002, leading some to think that local government does not share the Crown’s Treaty obligations.…”
Section: Discussionmentioning
confidence: 99%
“…According to the Treaty and contemporary resource management regulations, tangata whenua (local Indigenous people) have the right to exercise kaitiakitanga (Māori stewardship according to their own aspirations and practices). Māori, therefore, have the right to be included in planning and decision making for natural resources through co-management and co-governance arrangements Lundquist et al, 2016;Webster and Cheyne, 2017), though statutory requirements vary substantially from consultation to co-governance across different legislative Acts and institutional practices (Joseph et al, 2018). Māori rights under the Treaty extend to the right to redress for Crown breaches of the Treaty .…”
Section: Co-governance and Co-management Arrangementsmentioning
confidence: 99%